Thermo mechanical and microstructural constituents of dissimilar S700MC-S960QC high-strength steel welded joints using overmatched filler wire - Njock Bayock, Francois; Tony Kibong, Marius; Timba, Sadrack; Nelson Che, Nji (International Journal of Engineering and Technology, 2022)
In this study, a mechanical and microstructural constituent of welded joints of dissimilar high-strength and ultra-high-strength steels (S700MC/S960QC) using overmatched filler wire was evaluated. Three different heat inputs (18 kJ/cm, 8 kJ/cm, and 10 kJ/cm) and overmatched filler wire were applied using the GMAW process. Micro-hardness measurement was conducted using Vickers hardness test, tensile test, and microstructural constituents by scanning electron microscopy (SEM) and energy-dispersive X-ray spectroscopy (EDS) were performed in this analysis. A dissimilar welded sample with a cooling time of 51s (18 kJ/cm) showed a substantial hardness reduction in the fine grain heat-affected zone (HAZ) of the S700MC steel side, which was between 220-240 HV5. The cause could be the increase of heat input but also the use of overmatched filler wire, which can be the result of an increase of ferrite to austenite formation in the HAZ. SEM/EDS results confirmed the increase of carbide clusters, and tempered Martensite in the CGHAZ of the S960QC side, and ferrite-bainite on the S700MC side. An increase in the presence of high carbide content and the formation of Ni, Mo, and Mn were observed on the S960QC side. The increase of carbide formation in the CGHAZ of both sides reduced the hardness and strength of the welded joints. The tensile test confirms the softening observed in the FGHAZ of the S700MC side, which caused the joint fracture on this side during the test.Â Â